2008
DOI: 10.1038/nature07009
|View full text |Cite
|
Sign up to set email alerts
|

Charge self-regulation upon changing the oxidation state of transition metals in insulators

Abstract: Transition-metal atoms embedded in an ionic or semiconducting crystal can exist in various oxidation states that have distinct signatures in X-ray photoemission spectroscopy and 'ionic radii' which vary with the oxidation state of the atom. These oxidation states are often tacitly associated with a physical ionization of the transition-metal atoms--that is, a literal transfer of charge to or from the atoms. Physical models have been founded on this charge-transfer paradigm, but first-principles quantum mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
248
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(286 citation statements)
references
References 20 publications
33
248
0
2
Order By: Relevance
“…Under no circumstances can surface-adsorbed O Ã 2 be classified as a true integer anion [5]. Recently, Raebiger et al found that transition metal impurities inside bulk ionic or semiconducting crystals maintain nearly constant local charge during redox [20]. Here, we demonstrate a similar phenomenon in molecular adsorptions on metal surfaces.…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 72%
“…Under no circumstances can surface-adsorbed O Ã 2 be classified as a true integer anion [5]. Recently, Raebiger et al found that transition metal impurities inside bulk ionic or semiconducting crystals maintain nearly constant local charge during redox [20]. Here, we demonstrate a similar phenomenon in molecular adsorptions on metal surfaces.…”
Section: H Y S I C a L R E V I E W L E T T E R Ssupporting
confidence: 72%
“…A number of intriguing physical phenomena were revealed due to coexisting localized 3d impurity states. One of these is the "self-regulating response" [5,6], recently revisited by Raebiger et al [7], which shows that adding electrons to the 3d derived impurity levels does not change the integrated electron density around the 3d impurity atom because the orbitals of the surrounding ligand atoms rehybridize to minimize the impact of impurity charging. A second phenomenon is the "vacuum pinning rule," whereby transition levels of the same impurity atom in different host semiconductors line up in approximately the same way, regardless of the host chosen [8,9], thus permitting the deduction of band offsets between different pure materials from the knowledge of impurity level positions [10].…”
Section: Transition-metal Impurities In Semiconductorsmentioning
confidence: 99%
“…It is not even clear if substitutional TM atoms in the graphene sheet have magnetic moments. In general, simplistic assumptions about TM behavior are rarely valid, as their properties can vary widely in various hosts [8]. Furthermore, the precise knowledge of the TM-sp 2 -carbon interaction is important for understanding carbon nanotube growth [9], fuel cell properties [10], and the role of implanted magnetic atoms such as Fe in the development of magnetic order in carbon materials [11].…”
mentioning
confidence: 99%
“…The same accuracy was also achieved with respect to the k-point sampling over the Brillouin zone (with meshes up to 19 Â 19 k-points). This approach has been demonstrated to be adequate for the modeling of defects in graphitic systems [16] and TM impurities in various matrices [8,17].…”
mentioning
confidence: 99%